Sand extraction and coastal degradation in San-Pedro (south-west Ivory Coast) - Ahua, Emile Aurélien; Tanoh, Kouamé Perèze (Geografares, 2026)
Public policies regarding environmental preservation in the coastal city of San-Pedro face a crucial development in sand extraction activities. This activity, which has an economic dimension along the beach, bears the dual impacts of intense coastal urbanization and coastline erosion. Given the urgency of this situation, this study aims to understand the extent to which sand extraction can be practiced while reducing impacts on the coastline. To achieve this objective, this contribution analyzes the forces at play that embody the emergence of this activity through a mixed-method approach primarily focused on creating qualitative scenarios. Data was collected from 52 stakeholders, including workers, truck drivers, members of the village community, NGOs, private organizations, and local elected officials. Based on the results obtained, it is important to note that sand extraction, due to its economic and social productivity, exacerbates environmental degradation, particularly along the coastline. However, it is evident that there is currently a lack of local policies or strategies capable of integrating this activity within an ecological framework. That being said, awareness-raising, ecological transition, and corporate social responsibility prove to be key tools for simultaneously reducing coastal destruction and safeguarding this profession that sustains many in the city of San-Pedro.